A Systematic Robbery: Transforming the Memory, Culture, and Landscape of the Ukrainian Steppe - Iakovlenko, Kateryna (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2024)
The Russian Federation’s war of aggression against Ukraine, which began in 2014 with the annexation of the Crimea and the occupation of parts of the Donetsk and Luhansk oblasts, has brought the issues of memory and identity to the forefront of public discussion. In public discourse, the history of eastern Ukraine is primarily associated with the Soviet-era industrialization of the Donbas and the formation of the administrative borders of the Donetsk and Luhansk oblasts that accompanied it. However, the history of this region is considerably richer and extends to much earlier times. This article explores the ways in which violence has shaped eastern Ukraine’s social and cultural landscapes; its focus is on the kurhans (kurgans [“burial mounds”])—graves that were erected as early as five millennia ago and have existed in the landscape of the region ever since. Investigating the history of these graves involves engaging with centuries of commemorative traditions, colonialisms, and military violence. I look specifically at Soviet-propaganda approaches toward the incorporation and appropriation of burial-mound symbolism for the molding of local identity and memory politics. By analyzing the kurhans as elements of landscape, as memorials, and as poetic metaphors, I attempt to shed light on the process by which the land absorbs traumatic memories and becomes a monument to human tragedy, war, resettlement, and colonialism.